2014
DOI: 10.1016/j.bcp.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

BCNU-induced gR2 DEFECT mediates S-glutathionylation of Complex I and respiratory uncoupling in myocardium

Abstract: A deficiency of mitochondrial glutathione reductase (or GR2) is capable of adversely affecting the reduction of GSSG and increasing mitochondrial oxidative stress. BCNU [1, 3-bis (2-chloroethyl)-1-nitrosourea] is an anticancer agent and known inhibitor of cytosolic GR ex vivo and in vivo. Here we tested the hypothesis that a BCNU-induced GR2 defect contributes to mitochondrial dysfunction and subsequent impairment of heart function. Intraperitoneal administration of BCNU (40 mg/kg) specifically inhibited GR2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…However, achieving this thermodynamic equilibrium would require a marked decline in the intracellular GSH/GSSG ratio ( i.e., to a 1/1 ratio to drive 50% conversion of protein to glutathionylated form) [51, 52], which can occur only under extreme conditions. Pharmacologic inhibition of glutathione reductase 2 intensively increases mitochondrial GSSG/GSH ratio, enhancing S-glutathionylation of Complex I in vivo via thermodynamic mechanism [53]. In the myocardium of eNOS −/− mice, enhanced Complex I S-glutathionylation occurs at a relative high GSH/GSSG ratio (Table I); therefore, the mechanism of thiol-disulfide exchange is not likely.…”
Section: Discussionmentioning
confidence: 99%
“…However, achieving this thermodynamic equilibrium would require a marked decline in the intracellular GSH/GSSG ratio ( i.e., to a 1/1 ratio to drive 50% conversion of protein to glutathionylated form) [51, 52], which can occur only under extreme conditions. Pharmacologic inhibition of glutathione reductase 2 intensively increases mitochondrial GSSG/GSH ratio, enhancing S-glutathionylation of Complex I in vivo via thermodynamic mechanism [53]. In the myocardium of eNOS −/− mice, enhanced Complex I S-glutathionylation occurs at a relative high GSH/GSSG ratio (Table I); therefore, the mechanism of thiol-disulfide exchange is not likely.…”
Section: Discussionmentioning
confidence: 99%
“…11–14 DMPO has also been used to assay for mitochondria-derived normalO2·- generation by EPR. 13,15 Because of the short half-life of DMPO/ • OOH (t 1/2 ≈45 seconds) and the possibility that the normalO2·- adduct can decompose to give an • OH adduct, a superoxide dismutase (SOD)–sensitive 4-line spectrum of DMPO/ • OH is often detected. Therefore, a suitable SOD, polyethylene glycol–conjugated SOD (PEG-SOD), or SOD mimetic must be used to confirm that the detected DMPO/ • OH is dependent on the formation of normalO2·-.…”
Section: Measurement Of Superoxide Hydrogen Peroxide and Redox Statusmentioning
confidence: 99%
“…14,24 Ex vivo EPR spin trapping with DMPO has been used recently to quantify mitochondria-derived normalO2·- in the rat heart. 15 DEPMPO has been used extensively to investigate molecular mechanisms of ROS generation mediated by enzymes such as endothelial NOS (eNOS), 25 NADPH oxidases, xanthine oxidase, 26 and the mitochondrial electron transport chain in vitro. 2730 …”
Section: Measurement Of Superoxide Hydrogen Peroxide and Redox Statusmentioning
confidence: 99%
“…Earlier studies with isolated mitochondria of rat and murine hearts indicated that mitochondria produce large amount of • O 2 − under oligomycin-induced state 4 conditions, but • O 2 − generation is diminished under conditions of ADP-mediated state 3 and FCCP-mediated uncoupling [20, 22]. The results thus lend support to the hypothesis that the proton motive force is high, and substantially contributes to • O 2 − production when the activity of F 1 F 0 ATP synthase (F 1 F 0 ATPase) is low (state 2 conditions) or F 1 F 0 ATPase is inhibited (state 4 conditions).…”
Section: Introductionmentioning
confidence: 99%